Revitalisasi Pendidikan Jasmani Dalam Mengembangkan Motorik Kasar Anak Usia Dini - Laily Fitriani; Herlina Herlina; Zakir Burhan (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2025)
Early childhood physical education is a very important aspect in the development of children's cognitive, affective and psychomotor abilities towards the next level. The practice of early childhood physical education faces various problems from learning activities, facilities, social conditions and government policies that are less able to pay attention to physical education for early childhood. A structured physical education programme can help children develop gross motor skills, such as running, jumping and playing with a ball, which are important in children's physical and cognitive development.